Commercial Formulates of Trichoderma Induce Systemic Plant Resistance to Meloidogyne incognita in Tomato and the Effect Is Additive to That of the Mi-1.2 Resistance Gene - Pocurull, Miriam; Fullana, Aïda M.; Ferro, Miquel; Valero, Pau; Escudero, Nuria; Saus, Ester; Gabaldón, Toni; Sorribas, F. Javier (Frontiers in Microbiology, 2020)
Meloidogyne is the most damaging plant parasitic nematode genus affecting vegetable crops worldwide. The induction of plant defence mechanisms against Meloidogyne in tomato by some Trichoderma spp. strains has been proven in pot experiments, but there is not information for tomato bearing the Mi1.2 resistance gene or for other important fruiting vegetable crops. Moreover, Trichoderma is mostly applied for managing fungal plant pathogens but there is little information on its effect on nematode antagonistic fungi naturally occurring in soils. Thus, several experiments were conducted to determine: i) the ability of two commercial formulates of T. asperellum (T34) and T. harzianum (T22) to induce systemic resistance in tomato and cucumber against an avirulent M. incognita population in split-root experiments; ii) the effect of combining T34 with tomato carrying the Mi 1.2 resistance gene to an avirulent M. incognita population in sterilized soil; and iii) the effect of combining T34 with tomato carrying the Mi 1.2 resistance gene to a virulent M. incognita population in two suppressive soils in which P. chlamydosporia is naturally present, and the effect of T34 on the level of P. chlamydosporia egg parasitism. Both Trichoderma formulates induced resistance to M. incognita in tomato but not in cucumber. In tomato, the number of egg masses and eggs per plant were reduced in a 71% and 54% by T34, respectively. T22 reduced in a 48% the number of eggs per plant but not the number of egg masses. T34 reduced the number of eggs per plant of the virulent M. incognita population in both resistant and susceptible tomato cultivars irrespective of the suppressive soil, and its effect was additive with the Mi 1.2 resistance gene. The percentage of fungal egg parasitism by Pochonia chlamydosporia was not affected by the isolate T34 of T. asperellum.